Pseudoendemism in Mediterranean black flies (Diptera: Simuliidae): a new record for Africa - Haouchine, Sabrina; Belqat, Boutaïna; Adler, Peter H.; Lounaci, Abdelkader (Zootaxa, 2024)
The first record of a European black fly, Simulium ichnusae Rivosecchi & Contini, is documented for Africa, where it was found at elevations above 1000 m in the Djurdjura Mountains of Algeria. Considered an endemic species of Sardinia for 60 years, S. ichnusae must now be regarded as pseudoendemic. Larvae, pupae, females, and males from the Djurdjura Mountains compare well with those in the original description of the species. Chromosomally, S. ichnusae differs from the standard banding sequence of the S. vernum group by a transposed nucleolar organizer—the only known member of the group with this condition—and three fixed inversions, all of which are shared by other members of this species group. The addition of S. ichnusae to the Algerian fauna increases the number of nominal species of black flies known from the country to 34. The discovery of S. ichnusae suggests that additional trans-Mediterranean species await discovery in the coastal Mediterranean mountains and emphasizes that claims of endemism depend on thorough surveys and taxonomic accuracy.